S08. Electrical stimulation of SEEG and epileptic network connectivity. (May 2018) - Alwaki, Abdulrahman; Britton, Jeffrey; Gompel, Jamie Van
Abstract : Introduction: It has been estimated the two thirds of the human cortex lies in the sulci. Deep structures such as limbic structures, medial frontal, insular and orbital frontal regions are relatively inaccessible to subdural electrodes. Our case demonstrates the utility of Stereotactic EEG in localizing seizure onset zone and mapping the function of both cortical and subcortical structures in a patient with drug resistant focal epilepsy. Methods: The patient is a 58 year old right handed woman with a history of drug resistant epilepsy since age 18. Her seizures were predominantly nocturnal and arose out of sleep. She had multiple seizures per night. She reports out of body experience, anxiety feeling and chocking sensation followed by back and forth rocking movements. Seizures usually last 30–45 s with a quick recovery from her seizures. Her ictal scalp EEG was non localizing. Her interictal FDG PET scan was normal. Her subtracted ictal-interictal SPECT scan was also non localizing. Her epilepsy protocol 3T brain MRI showed a subtle area of white–grey matter blurring on the DIR pulse sequence which involved the left anterior cingulate gyrus. The patient underwent Stereotactic EEG implantation to confirm seizure localization and for functional mapping. Her ictal intracranial EEG showed an onset of high amplitude repetitive spiking intermixed with low amplitude fast activity in the electrodes located in the left anterior cingulate followed by spread of the same pattern to electrodes in the left insular cortex within less than 500 ms from the onset. Electrical stimulation mapping was performed. Biphasic 50 Hz stimulation starting at 1 mA intensity with increments of 0.5 mA was applied. Results: The patient reported the typical sensation of her aura and early symptoms of her seizures during the stimulation of left anterior cingulate contacts during stimulation with 1–3 mA which was reproducible. She also reported the usual sensation she experiences a few seconds following the onset of her seizures during the stimulation of her left insular electrodes during stimulation with 3–5 mA that was also reproducible. No after- discharge was seen during these stimulation trials. The patient subsequently underwent an open lesionectomy of the anterior cingulate MRI abnormality. Pathology showed focal cortical dysplasia type IIB with dysmorphic neurons and balloon cells. The patient has remained seizure free since surgery. No neurological deficit was seen. Conclusion: Electrical stimulation mapping of SEEG can be used to study the functionality of the cortex as well as the subcortical structures. In addition to localizing eloquent cortex, electrical stimulation of SEEG can support the localization of epileptic network and seizure onset zone.